Ecoteology Perspective in the Preservation of Bunker Together Malang as an Effort to Strengthen Environmental Ethics and Local History - Ardelia, Abida; Istiqomah, Adinda Dian; Khafsin, Ahmad Abi; Amalina, Sharfina Nur (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED), 2025)
Bunkers are colonial buildings that not only have architectural value, but also create relationships between humans, the environment and Allah SWT. In the modern era, often the perception of colonial buildings is seen as purely aesthetic, so it requires a new approach. This research aims to examine the preservation of the Bunker Bareng Malang through the perspective of ecotheology as an effort to strengthen environmental ethics and local historical awareness. This study uses a descriptive qualitative approach with field observation, interviews, and literature study methods. The results of the data were obtained from interpretive analysis to see the relationship between theological, social and ecological values in the process of building transformation. The Research results indicated that the functional transformation that occurred at Bunker Bareng Malang is an adaptive preservation, emphasizing the change from its original function as a defense system into a creative public space while still maintaining the original building structure and its historical value. Not only does it have an impact on the local economy, but this preservation also fosters ethical awareness for the younger generation of the importance of maintaining cultural heritage as a form of human spiritual responsibility towards nature and the creation of Allah SWT. Based on Islamic ecotheology, this study asserts that the ecotheological approach can be a sustainable step by harmonizing moral, ecological, and spiritual values through the principles of tawḥid and amanah as the ethical foundation for environmental conservation.